Pharmacogenetics of Statin-Induced Myotoxicity - Kee, Ping Siu; Chin, Paul Ken Leong; Kennedy, Martin A.; Maggo, Simran D. S. (Frontiers in Genetics, 2020)
Statins, a class of lipid-lowering medications have been the keystone treatment in cardiovascular health. However, adverse effects associated with statin use impact patient adherence, leading to statin discontinuation. Statin-induced myotoxicity (SIM) is one of the most common adverse effects, prevalent across all ages, genders and ethnicities. Although certain demographic cohorts carry a higher risk, the impaired quality of life attributed to SIM is significantly comparable. The pathogenesis of SIM remains to be fully elucidated, but it is clear that SIM is multi-factorial. These factors include drug-drug interactions, renal or liver dysfunction and genetics. Genetic-inferred risk for SIM was first reported by a landmark GWAS which reported a higher risk of SIM with a polymorphism in the SLCO1B1 gene. Since then, research associating genetic factors with SIM has expanded widely and has become one of the foci in the field of pharmacogenomics. This review provides an update on the genetic risk factors associated with SIM.